2023
DOI: 10.1021/acsbiomaterials.2c01148
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Enriched Cardiac Extracellular Matrix Hydrogel Promotes In Vitro Angiogenesis

Abstract: Angiogenesis is essential for cardiac repair after myocardial infarction. Promoting angiogenesis has been demonstrated as an effective approach for myocardial infarction treatment. Several different strategies for inducing myocardial angiogenesis have been explored, including exogenous delivery of angiogenic genes, proteins, microRNAs, cells, and extracellular vesicles. Various types of injectable hydrogels have been investigated for cardiac tissue repair. One of the most promising injectable hydrogels in card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…The use of extracellular matrix-based biomaterials has become increasingly popular for reconstructing the native tissue microenvironment . This is due to their ability to modulate therapeutic cells toward tissue-specific differentiation. , The multipotential BMSCs were encapsulated in our CdECM and hybrid hydrogels, and the cellular 3D environment drove chondrogenic differentiation of BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The use of extracellular matrix-based biomaterials has become increasingly popular for reconstructing the native tissue microenvironment . This is due to their ability to modulate therapeutic cells toward tissue-specific differentiation. , The multipotential BMSCs were encapsulated in our CdECM and hybrid hydrogels, and the cellular 3D environment drove chondrogenic differentiation of BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 48 , 49 , 50 ] In addition, it was also proven that ECM also obtained improved angiogenic capacity. [ 51 ] Ki67, an important marker of cell proliferation, was also evaluated in wound samples at day 7 and day 14 to estimate total cellular proliferation. The immunostaining results of Ki67 showed that the expression of Ki67 increased significantly in the ECM@exo group compared with the other groups, while the control group had few positive cells (Figure 4I,K ).…”
Section: Resultsmentioning
confidence: 99%
“…BMs that support the attachment, growth, and function of CMs are highly desired for both research and clinical purposes. Typical BMs for CMs include natural polymers (e.g., alginate, collagen, gelatin, chitosan, hyaluronic acid, and extracellular matrix (ECM)), synthetic polymers (e.g., polyethylene glycol, polylactide, polyurethane, poly­( N -isopropylacrylamide), polycaprolactone, poly­(lactic- co -glycolic acid)), and hybrid BMs. , These materials can be fabricated in various forms, such as hydrogels and fibrous and porous scaffolds, to provide necessary microenvironments in support of CM growth. The introduction of growth factors, exosomes, and other bioactive moieties in BMs would bring additional benefits to CMs . Different biomaterials can also be grafted or mixed at certain ratios to achieve a better performance …”
Section: Transcriptomic Approaches In Cardiomyocyte–biomaterials Rese...mentioning
confidence: 99%